Loxenatide Alleviates High Glucose-Induced Pancreatic β-Cell Senescence via Regulating the PERK/eIF2α Pathway - Yuan, Junfang; Wang, Yuzhong; Wang, Defeng; Yan, Han; Wang, Ning (Hormone and Metabolic Research, 2024)
Glucagon-like peptide-1 (GLP-1) receptor agonists are effective hypoglycemic agents for type 2 diabetes mellitus (T2DM). It was reported that T2DM was implicated in pancreatic β-cell senescence. Whether loxenatide regulates cellular senescence of pancreatic β-cells is to be investigated. Our results revealed that high glucose (HG)-induced cellular senescence and elevated expression of SASP factors inhibited cell proliferation and stimulated DNA damage, which were reversed by loxenatide treatment. In addition, HG induction resulted in promoted insulin secretion and insulin synthesis of pancreatic β-cells and loxenatide treatment further strengthened these influences. In addition, loxenatide could inactivate the PERK/eIF2α signaling pathway via decreasing the levels of p-PERK and p-eIF2α in HG-induced pancreatic β-cells. Furthermore, CCT020312, an activator of the PERK/eIF2α signaling pathway, abolished loxenatide-mediated inhibiting cellular senescence, elevating cell proliferation and improving DNA damage and enhancing insulin secretion of HG-induced pancreatic β-cells. In conclusion, our results indicated that loxenatide impeded cellular senescence, promoted cell proliferation, improved DNA damage, enhanced insulin secretion and insulin synthesis of HG-induced pancreatic β-cells through modulating the PERK/eIF2α signaling pathway.
Keywords: loxenatide; cellular senescence; insulin secretion; the PERK/eIF2α signaling pathway; type 2 diabetes mellitus